2018
DOI: 10.31217/p.32.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Efficiency of Transport and Logistics Infrastructure of Railway Transport

Abstract: The high level of logistics development positively affects many socio-economic indicators of the country’s economic development, such as inflation rates, productivity indicators, etc. Increasing productivity through the use of logistics at enterprises has a positive impact on the competitiveness in global markets, as well as on profit level. The aim of this article is to analyze the evolution of productivity in rail transport among several countries from 1997 to 2016. We use a non-parametric approach that allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…At present, the research fields using coupling coordination degree model in China mainly focus on provinces [44,45], regions [46,47], and industries [11,40,48], such as urbanization and logistics industry [27,29,43,45], urban and rural economic development and ecological environment [47,49], economic growth and environmental pollution [50,51], pharmaceutical manufacturing industry and regional economy [20,44,47,52], the innovation drive with high quality and economic development [53,54], the sustainable development of regional economy [55,56], science and technology innovation [57,58], integrated transportation and logistics industry and financial industry [29,35], rural revitalization and new type of urbanization [43,45,59], the logistics industry and the new urbanization [45,60], and so on. In addition to this method often used to study coupling coordination degree of two systems, there are also some studies of three systems, such as the coordinated development of economy, society, environment [27,61] and tourism, urbanization, urban ecological environment [53,62], etc.…”
Section: Coupling Coordination Degree Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the research fields using coupling coordination degree model in China mainly focus on provinces [44,45], regions [46,47], and industries [11,40,48], such as urbanization and logistics industry [27,29,43,45], urban and rural economic development and ecological environment [47,49], economic growth and environmental pollution [50,51], pharmaceutical manufacturing industry and regional economy [20,44,47,52], the innovation drive with high quality and economic development [53,54], the sustainable development of regional economy [55,56], science and technology innovation [57,58], integrated transportation and logistics industry and financial industry [29,35], rural revitalization and new type of urbanization [43,45,59], the logistics industry and the new urbanization [45,60], and so on. In addition to this method often used to study coupling coordination degree of two systems, there are also some studies of three systems, such as the coordinated development of economy, society, environment [27,61] and tourism, urbanization, urban ecological environment [53,62], etc.…”
Section: Coupling Coordination Degree Modelmentioning
confidence: 99%
“…e academic research on the relationship between logistics industry and economic system has achieved fruitful results. e related research mainly focuses on the supply chain management [3][4][5][6], enterprise logistics performance [7][8][9][10], logistics infrastructure [11][12][13][14], green logistics [15][16][17][18][19], the interactive development of logistics industry, manufacturing industry and retail industry [20,21], and the evaluation index of logistics industry development [22,23]. However, spatial pattern study of logistics industry and economic interaction coupling coordination is less, and the influence factor of these is much rarer.…”
Section: Introductionmentioning
confidence: 99%
“…Saparovna Mukhtarova et al (2018) used a nonparametric method to evaluate the railway transportation productivity in multiple countries and found that productivity growth was concentrated from 1997 to 2016, with the productivity increases being mainly due to technological progress. It was also found that the higher the railway transportation autonomy and financial independence, the higher the infrastructure and technological change efficiencies.…”
Section: Literature Reviewmentioning
confidence: 99%